The Effect of Person-Job and Person-Organization Fit on Turnover Intentions: A Relationship Moderated by Organizational Culture - Cesário, Francisco; Sabino, Ana; Saldanha, Joana (Journal of Cultural Analysis and Social Change, 2026)
Purpose: In this study, we present four main goals. The first two goals aim to deep-in the link between Person-Job and Person-Organization Fit with Turnover Intentions. To do so, we aim to (1) verify if Person-Job Fit, Person-Organization Fit and Turnover Intentions change according to some demographic and employment variables and (2) verify if Person-Job Fit and Person-Organization Fit influence Turnover Intentions. We also aim to understand the role Organizational Culture plays in these relationships by (3) analyzing the moderating role of organizational culture on the relationship between Person-Job Fit and Turnover Intentions and between Person-Organization Fit and Turn-over Intentions and (4) deep-in on the possible differences between the four organizational cultures by demographic and employment characteristics. Design/methodology/approach: The study involved a sample of 210 workers from companies operating in Portugal. Findings: The results indicate significant differences according to some demographics in Turnover Intentions and Person-Job Fit. We also verified that Person-Job Fit and Person-Organization Fit negatively influence Turnover Intentions. Finally, we found that only Adhocracy Culture moderates the relationship between Person-Job Fit and Turnover Intentions. Originality: Not only this study reinforces the negative influence of Person-Job Fit and Person-Organization Fit on Turnover Intentions, but it also innovates by analyzing the role of organizational culture in these dynamics.